Optimizing Physical Conditioning Programs for Badminton Athletes: A Comprehensive Review of Training Strategies - A Systematic Review - Fadli Ihsan; Ahmad Nasrulloh; Sigit Nugroho; Zhanneta Kozina (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Study Background and Objectives: The performance of international badminton athletes is shaped by a blend of physical, psychological, technical, and tactical factors. This study seeks to systematically analyze these essential elements, driven by the imperative to comprehend critical factors for crafting optimized training programs to achieve peak performance efficiently and effectively.Materials and Methods: This study used a systematic approach to review various literature sources, journal articles, and empirical studies related to the achievements of badminton athletes at the international level. Strict inclusion and exclusion criteria were applied to ensure that only high-quality studies were included in the analysis. The data collected was then comprehensively analyzed to identify critical factors that consistently influence badminton athlete performance. Results: This systematic analysis reveals that the main factors influencing badminton athletes' achievements at the international level involve a combination of physical, psychological, technical, and tactical aspects. Physical strength, mental resilience, technical expertise, and a deep tactical understanding proved essential in achieving success in the sport. A deep understanding of match dynamics, emotional management, and adaptation to the opponent's tactics were also found to be keys to success. Conclusion: The results of this analysis provide a holistic view of the factors that significantly influence the performance of badminton athletes at the international level. The practical implications include the development of more focused and adaptive training programs, as well as more intensive psychological approaches. These conclusions provide an essential contribution for coaches, researchers, and decision-makers in badminton to improve athletes' potential and results at the international level.